2018
DOI: 10.1098/rsta.2017.0417
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigation of mechanisms for phase mixing in olivine + ferropericlase aggregates

Abstract: To investigate the role of grain boundary pinning and the mechanisms by which phase mixing occurs during deformation of polymineralic rocks, we conducted high-strain torsion experiments on samples consisting of olivine plus 30 vol% ferropericlase. Experiments were performed in a gas-medium deformation apparatus at 1524 K and 300 MPa. Samples were deformed to outer radius shear strains of up to γ ( R ) = 14.1. The value of the stress exponent and the small grain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…At lithosphere like stress and temperature conditions, the model predicts the formation of rapidly deforming strongly localized ultramylonitic bands embedded within coarser grained, poorly mixed or monomineralic, slowly deforming regions (Figure c). The coexistence of the well‐mixed weak regions and the poorly mixed strong regions is in agreement with the hysteretic branches predicted by Bercovici and Ricard (), as well as the experimental observations of Cross & Skemer (; see also Figure d) and Wiesman et al ().…”
Section: Newest Directionssupporting
confidence: 91%
See 3 more Smart Citations
“…At lithosphere like stress and temperature conditions, the model predicts the formation of rapidly deforming strongly localized ultramylonitic bands embedded within coarser grained, poorly mixed or monomineralic, slowly deforming regions (Figure c). The coexistence of the well‐mixed weak regions and the poorly mixed strong regions is in agreement with the hysteretic branches predicted by Bercovici and Ricard (), as well as the experimental observations of Cross & Skemer (; see also Figure d) and Wiesman et al ().…”
Section: Newest Directionssupporting
confidence: 91%
“…The effectiveness of Zener pinning, however, is controlled by the degree to which the different phases are interspersed or mixed with each other at the grain scale. The process of phase mixing, and its effect on rock rheology and shear localization, have been the focus of numerous recent experimental and theoretical studies (Bercovici & Mulyukova, ; Bercovici & Ricard, ; Bercovici & Skemer, ; Cross & Skemer, ; Tasaka et al, ; Tasaka et al, ; Wiesman et al, ). At low pressures (i.e., <1 GPa), intergrain mixing may occur by chemical or metamorphic reactions (Platt, ; Czertowicz et al, ; Précigout & Stünitz, ) and brittle processes (Dimanov et al, ), all of which typically involving cavitation.…”
Section: Newest Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous deformation experiments using two-phase aggregates demonstrated that strain weakening is associated with grain size reduction resulting from phase mixing in olivine-pyroxene systems (Farla et al, 2013;Hirauchi et al, 2016;Precigout & Stunitz, 2016;Tasaka, Zimmerman, Kohlstedt, Stunitz, & Heilbronner, 2017), olivine-ferropericlase systems (Wiesman et al, 2018), and calcite-halite systems (Cross & Skemer, 2017). Especially for peridotites, several mixing mechanisms have been proposed including dynamic recrystallization, geometrical mixing due to grain boundary sliding, formation of cavities leading to nucleation of new grains under hydrous conditions, formation of new hydrous phases due to reaction of minerals, severing of new grains formed at triple junctions coupled with their transport along grain boundaries, severe shear thinning of individual phases, and stress-driven diffusion processes (Bercovici & Skemer, 2017;Cross & Skemer, 2017;Farla et al, 2013;Hirauchi et al, 2016;Linckens et al, 2014;Precigout & Stunitz, 2016;Tasaka, Zimmerman, Kohlstedt, Stunitz, & Heilbronner, 2017).…”
Section: Introductionmentioning
confidence: 99%